Micellized Protein Transduction Domain-Bone Morphogenetic Protein-7 Efficiently Blocks Renal Fibrosis Via Inhibition of Transforming Growth Factor-Beta–Mediated Epithelial–Mesenchymal Transition - Kim, Seonghun; Jeong, Cheol-Hee; Song, Sang Hyun; Um, Jo Eun; Kim, Hyun Sil; Yun, Jun Seop; Han, Dawool; Cho, Eunae Sandra; Nam, Bo Young; Yook, Jong In; Ku, Minhee; Yang, Jaemoon; et al. (Frontiers in Pharmacology, 2020)
Tubulointerstitial renal fibrosis is a chronic disease process affecting chronic kidney disease (CKD). While the etiological role of transforming growth factor-beta (TGF-β) is well-known for epithelial-mesenchymal transition (EMT) in CKD, effective therapeutics for renal fibrosis are largely limited. As a member of the TGF-β superfamily, the bone morphogenetic protein-7 (BMP-7) plays an important role as endogenous antagonist of TGF-β, inhibiting fibrotic progression in many organs. However, soluble rhBMP-7 is hardly available for therapeutics due to its limited pharmaco-dynamic profile and rapid clearance in clinical settings. In this study, we have a developed novel therapeutic approach with protein transduction domain (PTD) fused BMP-7 in micelle (mPTD-BMP-7) for long-range signaling in vivo. Contrary to rhBMP-7 targeting its cognate receptors, the nano-sized mPTD-BMP-7 is transduced into cells through an endosomal pathway and secreted to the exosome having active BMP-7. Further, transduced mPTD-BMP-7 successfully activates SMAD1/5/8 and inhibits the TGF-β-mediated EMT process in vitro and in an in vivo unilateral ureter obstruction (UUO) model. To determine the clinical relevance of our strategy, we also developed an intra-arterial administration of mPTD-BMP-7 through renal artery in pigs. Interestingly, the mPTD-BMP-7 through renal artery intervention effectively delivered into Bowman’s space and inhibits UUO-induced renal fibrosis in pigs. Our results provide a novel therapeutic targeting TGF-β-mediated renal fibrosis and other organs as well as a clinically available approach for kidney.